Quantum beats of free and bound excitons in GaN - Kyhm, K; Taylor, R; Ryan, J; Aoki, T; Kuwata-Gonokami, M; Beaumont, B; Gibart, P (2001)
We present spectrally resolved and time-integrated four-wave mixing measurements at coherent dynamics of bound excitons in a high-quality GaN epilayer. Coherent excitation, with co-circular polarized light, of the neutral donor-bound excitons (D 0X) and A excitons (XA) results in quantum beats, corresponding to the energy splitting between D 0X and XA. The temperature-dependent dephasing rate is used to deduce the strength of the D 0X-acoustic-phonon interaction via the homogeneous linewidth. © 2001 American Institute of Physics.